Mortality trend of cancer and main types according to macroregion in the state of Mato Grosso, Brazil, 2000 to 2015 - Luísa Bertoldi Aguilar; Camila Vieira Gomes; Geraldo Soares de Lima Neto; Letícia Helena Ferreira Montenegro; Jânia Cristiane de Souza Oliveira; Noemi Dreyer Galvão; Francine Nesello Melanda; Mário Ribeiro Alves; Bárbara da Silva Nalin de Souza (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT: Objective: To describe the mortality trend from all cancers and the five main ones in the state of Mato Grosso, Brazil, from 2000 to 2015. Methods: This is a descriptive, ecological, time series study, with data referring to deaths of residents of Mato Grosso due to cancer (ICD-10 codes C00 to C97), from the Mortality Information System (SIM). Time trend analyses of the standardized mortality rate from all cancers and five specific cancers (lung, prostate, breast, colorectal and cervical) for the state and according to macroregion (South, West, North, East and Center-North) were performed using linear regression (p<0.05). Results: From 2000 to 2015, 28,525 deaths from all cancers in residents of the state of Mato Grosso were recorded. An increasing trend was observed for all cancers, in addition to lung, breast and colorectal cancers. The South and North macroregions showed an increasing trend for all cancers, breast and colorectal, and Center-North for breast and colorectal. East showed an increasing trend for all cancers, prostate and colorectal, and decreasing for cervical. Conclusion: In the state of Mato Grosso, there was an increasing trend in mortality for all cancers and from specific ones, with emphasis on breast and colorectal cancer in most macroregions.